Nrg1 and Nrg2 Transcriptional Repressors Are Differently Regulated in Response to Carbon Source - Berkey, Cristin D. (American Society for Microbiology, 2004)
The Nrg1 and Nrg2 repressors of Saccharomyces cerevisiae have highly similar zinc fingers and closely related functions in the regulation of glucose-repressed genes. We show that NRG1 and NRG2 are differently regulated in response to carbon source at both the RNA and protein levels. Expression of NRG1 RNA is glucose repressed, whereas NRG2 RNA levels are nearly constant. Nrg1 protein levels are elevated in response to glucose limitation or growth in nonfermentable carbon sources, whereas Nrg2 levels are diminished. Chromatin immunoprecipitation assays showed that Nrg1 and Nrg2 bind DNA both in the presence and absence of glucose. In mutant cells lacking the corepressor Ssn6(Cyc8)-Tup1, promoter-bound Nrg1, but not Nrg2, functions as an activator in a reporter assay, providing evidence that the two Nrg proteins have distinct properties. We suggest that the differences in expression and function of these two repressors, in combination with their similar DNA-binding domains, contribute to the complex regulation of the large set of glucose-repressed genes.